Errata: Background of Extended-Spectrum Beta-lactamase (ESBL) Producers Isolated in One Japanese University Hospital - UGAJIN, Kazuhisa; HIISHI, Ayumi; ANAN, Akiko; ARAI, Yuuji; NAKAMURA, Hisako; MARUMO, Kenji; TAGUCHI, Kazumi; KAWANO, Rumiko; NAGASHIMA, Goro (Japanese Journal of Infection Prevention and Control, 2011)
Japanese Journal of Environmental Infections, Vol. 26, No. 4 (2011), pp.228-233